CLINICAL CHARACTERISTICS OF DYSPEPSIA SYNDROME IN PATIENTS WITH TYPE 2 DIABETES MELLITUS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
To estimate the prevalence of dyspepsia and to study its clinical manifestations and risk factors in patients with type 2 diabetes mellitus. One hundred and seven patients with type 2 DM and 33 with functional dyspepsia were examined. A clinical and laboratory study and testing were made to identify the symptoms of dyspepsia; dyspepsia-associated factors were studied. Dyspepsia was observed in 71.0 % of the examined patients with type 2 DM. It may be attributed to organic gastrointestinal tract (GIT) diseases only in 42.3% of cases. In the type 2 DM patients, dyspepsia that could not be explained by organic GIT diseases was mainly manifested by a dyskinetic type while an ulcer-like type was prevalent in those with organic GIT diseases. In the patients with type 2 DM, dyspepsia that could not be accounted for GIT diseases was associated with the duration of carbohydrate metabolism disturbance, the presence of diabetic complications, Helicobacter pylori infection, and patient age. Some symptoms of dyspepsia (repletion and epigastric discomfort), which could not be explained by organic GIT diseases in patients with type 2 DM were associated with diabetic complications and carbohydrate metabolic parameters. Dyspepsia in type 2 DM was observed in 71% of cases; it can be due to organic GIT diseases in 42.3% and its association with digestive organ pathology was not revealed in 57.7%.